Design Method of ICPS Comprehensive Security Controller With Multi-Target Constraints and DoS Intrusion Tolerance Capability Driven by Double End ADETCS - Yajie Li; Feiping Wang (IEEE Access)
With a focus on industrial cyber-physical systems (ICPSs) that are subject to dual-ended denial-of-service (DoS) attacks and actuator faults, and in the context of a double-ended adaptive discrete event-triggered communication scheme (ADETCS), we study the design method of ICPS comprehensive security controller with multi-target constraints. Firstly, a novel double-ended ADETCS is designed to double-screening the transmitted data on both the sensing and execution sides, and a comprehensive security control architecture based on ICPSs with multi-objective constraints that can simultaneously resist dual-ended DoS attacks and actuator failures has been constructed. Secondly, on the sensing side, a method based on integration of data driven and model mechanisms is used to deal with DoS attacks with different levels of severity. On the execution side, a Principal Component Analysis - Long Short-Term Memory (PCA-LSTM) data-driven method is used to reconstruct and compensate the lost data caused by DoS attacks. Thirdly, by introducing multi-target constraints, such as $α $ -stability and $H_{∞ }$ performance index, and based on the constructed Lyapunov-Krascovskii function, a cooperative design method is derived for the observer and the comprehensive security controller under multi-target constraints. Finally, the effectiveness and practicability of the proposed method are verified by a simulation experiment involving an industrial four-capacity water tank. The results indicate that the integration method of data driven and model mechanisms enhances the ability of ICPSs to resist dual-ended DoS attacks, and the double-ended ADETCS further saves network communication resources.